Effects of Short Term and Long Term Usage of Patellar Kinesio Taping on Patellar Position in Women with Patellofemoral Pain Syndrome - Mahboobeh Banejad; Alireza Sarmadi; Firooz Maddadi (Shiraz University of Medical Sciences, 2016)
Background: Patellar mal tracking is responsible for pain and disability in patellofemoral pain syndrome (PFPS). Patellar kinesio taping may have different effects on short and long term usage. The aim of this study is to compare the effect of short term and long term patellar kinesio taping in patellar position on women with patellofemoral pain syndrome using Magnetic Resonance Imaging (MRI). Methods: Thirty women with a mean age of 32.2 ± 6.18 years with one year history of PFPS participated in this study. All participants provided written, informed consent. MRI was taken three times from participant's patellofemoral joint: 1) Without taping, 2) Immediately after taping in the first session, 3) After 10 sessions of taping. The effectiveness of the interventions was determined by measuring the patellofemoral congruence angle (PFCA), lateral patellofemoral angle (LPFA), and lateral patellar displacement (LPD) on MRI images. Results: Statistical analysis showed that utilizing kinesio taping in short time and after 10 sessions, significantly changed PFCA and LPD - except for PFCA after 10 sessions. Moreover, taping didn't have any significant effect to alter LPFA. Conclusion: In short term, mechanical effects of kinesio taping influenced the patella position but in long term, neuromuscular effects may be more effective than each one separately to alter patella position.